Training and injury profiles of international race walkers - Hanley, B. (New Studies in Athletics, 2014)
The high training volumes associated with elite race walking might result in better performances but they also increase the risk of injury. The purpose of this retrospective study was to survey training habits and injury prevalence amongst international race walkers. Self-administered questionnaires designed to record competitive performances, typical training practices, injury sites and occurrences were completed by 112 race walkers from 28 nations. On average, the men responding covered 125km of race walking across nine weekly training sessions, while the women covered 84km over seven sessions. Aside from these sessions, most athletes took part in running (80%) and resistance training (64%). The most commonly used training surfaces were roads (98%) and athletics tracks (68%). Injuries to the hamstrings, knees, feet and shins were the most frequently reported with more than half of cases requiring medical treatment and/ or time off training. The author concludes with a discussion of the survey findings and recommendations on range of points that include the importance of speed training and shorter distance performances, the use of softer training surfaces, and suggestions for preventing injuries at various specific locations.